2019
DOI: 10.1101/836304
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heme synthesis inhibition blocks angiogenesis via mitochondrial dysfunction

Abstract: The relationship between heme metabolism and angiogenesis is poorly understood. The final synthesis of heme occurs in mitochondria, where ferrochelatase (FECH) inserts Fe 2+ into protoporphyrin IX to produce proto-heme IX. We previously showed that FECH inhibition is antiangiogenic in human retinal microvascular endothelial cells (HRECs) and in animal models of ocular neovascularization. In the present study, we sought to understand the mechanism of how FECH and thus heme is involved in endothelial cell functi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In addition, endothelial specific PHGDH deletion led to vascular defects with decreased glutathione and NADPH synthesis in vivo (69), suggesting serine synthesis is essential for heme production in endothelial cells. Further, heme depletion selectively reduced the protein expression and activity of components of the mitochondrial electron transport chain, which could lead to enhanced mitochondrial dysfunction in endothelial cells (69)(70)(71). It will be interesting to ascertain the downstream interactions of hemoproteins upon FECH depletion in retinal and choroidal angiogenesis mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, endothelial specific PHGDH deletion led to vascular defects with decreased glutathione and NADPH synthesis in vivo (69), suggesting serine synthesis is essential for heme production in endothelial cells. Further, heme depletion selectively reduced the protein expression and activity of components of the mitochondrial electron transport chain, which could lead to enhanced mitochondrial dysfunction in endothelial cells (69)(70)(71). It will be interesting to ascertain the downstream interactions of hemoproteins upon FECH depletion in retinal and choroidal angiogenesis mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, defects in heme synthesis result in the accumulation of its intermediates leading to porphyria [8]. In addition, previous studies have shown that heme synthesis declines with age and its deficiency leads to mitochondrial dysfunction and iron accumulation leading to oxidative stress [9,10]. On the other hand, deficiency of heme oxygenases, enzymes that are necessary for heme degradation, has been implicated in the development of several age-related disorders, such as Alzheimer's disease, cancer as well as cardiovascular and metabolic diseases [11].…”
Section: Introductionmentioning
confidence: 99%